Pengukuran Ergonomi Metode ROSA pada Bagian CCR (Finish Mill) di PT X - Diah Andianingsari (LPPM Universitas Bina Sarana Informatika, 2022)
In the work of supervising the production process in front of the monitor screen, there is an inappropriate body position between humans, monitors and their work equipment. In the CCR Finish Mill) – Mr. Dida E., workers use computers. The results of the ROSA measurement that have been carried out have a value of 5 (five) with the result that it has a high level of risk that requires immediate changes. The highest level of risk was obtained from the assessment of the backrest that was far back, the work table surface that was too high, and the position of the mouse that was far from the worker's body. A high level of risk can lead to potential work accidents and occupational diseases in workers in the workplace. Corrective actions that can be taken so that potential work accidents and occupational diseases can be avoided are preventing fatigue or damage to the eyes by applying the 20:20:20 principle, stretching muscles after 2 hours, adjusting the position of the backrest so that it is not too far back (if possible ) or adding padding at the waist, increasing the height of the chair and positioning the mouse close to the worker's body so that the mouse is not too far away, adding a footrest if the worker's legs are lifted as a result of the height of the chair being raised. Keyword: ergonomic, musculoskeletal disorders,finish mill, ROSA, risk